2022
DOI: 10.36311/jhgd.v32.13318
|View full text |Cite
|
Sign up to set email alerts
|

Vascular accesses for hemodialysis in Ceará-Brazil

Abstract: Backgroung: the ideal access for hemodialysis is represented by arteriovenous fistulas both as initial access and in use and are determinants of health care parameters for chronic renal patients. Objective: to evaluate vascular access for hemodialysis. Methods: this is a cross-sectional study, with a sample of 2513 individuals on hemodialysis in Ceará. Data were collected on age, sex, time of treatment, underlying disease, initial access and access in use. The data were divided into two groups, the interior of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Besides, worldwide, kidney replacement therapy is more commonly provided to men than women, possibly due to biological factors and the accelerated development of chronic kidney disease in men. The current result was similar to Liu et al, [35] and Lima et al, [36] who noticed that 50% of respondents were males. Pertaining to residence, the current research results proved that approximately three quarters of the participants originated from rural regions.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, worldwide, kidney replacement therapy is more commonly provided to men than women, possibly due to biological factors and the accelerated development of chronic kidney disease in men. The current result was similar to Liu et al, [35] and Lima et al, [36] who noticed that 50% of respondents were males. Pertaining to residence, the current research results proved that approximately three quarters of the participants originated from rural regions.…”
Section: Discussionsupporting
confidence: 91%
“…In the findings by Lima et al, 26 , arteriovenous fistulas are more frequent as initial accesses in the metropolitan region of the state of Ceará, Brazil than in the interior of that state, with equivalence of fistulas in use in both regions. Catheter is the main initial access route.…”
Section: Discussionmentioning
confidence: 88%
“…Catheter is the main initial access route. The evaluation of vascular accesses in Ceará demonstrated that hemodialysis services are able to maintain good care parameters for patients with chronic kidney disease 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study in a northeast state of Brazil, which included 2,513 HD patients (18 HD centers), found an AVF prevalence of 79.6%, AVG of 0.9%, NTC of 15.0%, and TC of 4.5%. Nevertheless, in the study sample, catheters constituted 89% of the initial vascular access cases ( 9 ). In 2003, Linardi et al.…”
Section: Discussionmentioning
confidence: 99%